Awareness And Knowledge Of The Hospitality Instructors Of Probiotic Beverages ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: In today’s world there is an imbalance in the intestinal bacteria. Sedentary  lifestyle and poor sleeping schedule have affected our entire body. Apart from that we are regularly consuming unhealthy diets which are low in fiber and high in processed foods and  added sugar. Intake of probiotics will be led to the development of intestinal immune system  which regulates the intestinal bacteria. Objectives: To check the awareness and knowledge  of the Food & Beverage Instructors working in Hospitality Institutions/colleges/universities  about probiotic beverages and to check the need of incorporating the concept of probiotics in  the curriculum of the hospitality students. Methodology: To fulfill the objective of this  research paper we used both primary and secondary data. Numbers of respondent were 77.  The respondents were Food and Beverage department instructors working at different  Institutes of Hotel Management across India. For primary data collection, a structured  questionnaire was designed and sent to Food and Beverage  instructors/trainers/lecturers/teachers in the hospitality institutes. Percentage Analysis was  done for the calculation of data. Results: The faculty members are very well aware about the  concept of probiotic beverages. The results clearly state that not much attention has been  paid to the concept as most of the faculty members have not taken theory and practical  classes on this topic. However, they intend to take this concept in the future. Conclusion: It  can be concluded that despite the knowledge that the faculty members have, for probiotic  beverage more attention needs to be given on teaching the concept of probiotic to the  hospitality students as due to the current scenario customers are more inclined towards the  beverages which along with satisfying their palate provides nutritional benefits to them.
Keywords: Functional Beverages; Probiotics; Nutritional Value; Hospitality Instructors